PENURUNAN KANDUNGAN BESI (Fe) DAN MANGAN (Mn) PADA AIR SUMUR MENGGUNAKAN MEMBRAN KERAMIK - Sari, Merdiana; Purwoto, Setyo (WAHANA, 2018)
Increased population growth will put great pressure on the availability of water resources. For areas that have not received clean water services from PAM, people generally use groundwater (wells). Problems arise that is often found that the quality of groundwater used by the community is less qualified. Trying to overcome the problem then do the research decrease of heavy metal content Fe and Mn by using ceramic membrane. The aims of this study were: a) Looking for the most effective ceramic membrane composition of sawdust composition of 3%, 5% and 7% in reducing Fe and Mn levels in groundwater; b) Knowing the efficiency of ceramic membranes; c) Knowing the effective operation time of the variation of operating time is 1 hour, 2 hours and 3 hours. Ceramic membranes are made with a diameter of 10 cm and a thickness of 1.5 cm. Variations of the composition of the ceramic membrane to be tested are composition I (300) ie 5000gram clay, 500gram quartz sand, 150gram sawdust; composition II (500) ie 5000gram clay, 500gram quartz sand, 250gram sawdust and composition III (700) ie 5000gram clay, 500gram quartz sand, 350gram sawdust. The results showed that the ceramic membrane 700 was able to reduce Fe content in ground water up to 1,981 mg / L and Mn level up to 0,995 mg / L. Keywords: Water Supply, Ceramic Membrane, Heavy Metal Fe, Heavy Metal Mn